Diversity study and influence of apiculture flora on honey production in the municipality of Parelhas-RN - de oliveira Lima Júnior, Ivan; Lausanne Fontgalland, Isabel (Seven Editora, 2023)
The Brazilian semiarid has a floristic diversity of very interesting apicultural benefits, which can directly influence the productive results of such activity. In this context, the present work aimed to analyze the apicultural flora in two different realities (anthropized area and preserved area) and its influence on honey production. The municipality of Parelhas, where the experiment was located, is in the Seridó Potiguar microregion, in the southern center of RN. For this experiment, 30 Langstroth standard hives were used, divided into two nuclei of 15 hives each. They were about 2km apart. From September 1, 2018, to January 20, 2019, all colonies were weekly fed with 800ml of 1:1 water syrup and sugar. The old wax was changed to honeycomb wax in all hives. During flowering, a floristic survey of the surroundings of both areas studied was made differently. In the surroundings of nucleus 1, 46 botanical species of apiculture interest were found, and 12 species around nucleus 2. Regarding honey production, nucleus 1 presented an average of 37 kg per hive and 2 presented 5 kg. After all the procedures we verified that only core 01 obtained a higher honey production, and the results in this core were satisfactory. DOI: https://doi.org/10.56238/devopinterscie-122